Listening to the autistic voice: Mental health priorities to guide research and practice in autism from a stakeholder-driven project. (May 2020) - Benevides, Teal W; Shore, Stephen M; Palmer, Kate; Duncan, Patricia; Plank, Alex; Andresen, May-Lynn; Caplan, Reid; Cook, Barb; Gassner, Dena; Hector, Becca Lory; Morgan, Lisa; Nebeker, Lindsey; et al.
Autistic adults are significantly more likely to experience co-occurring mental health conditions such as depression and anxiety. Although intervention studies are beginning to be implemented with autistic adults to address mental health outcomes, little is known about what research autistic adults feel is needed, or what mental health outcomes are of value to them. The purpose of this article is to describe a project that involved more than 350 autistic adults and other stakeholders as coproducers of research priorities on mental health. Through a variety of methods including a large online survey, two large stakeholder meetings, and three face-to-face focus groups, the project team identified five top priorities for mental health research which should be incorporated by researchers and practitioners in their work with autistic adults. These included research to inform trauma-informed care approaches; societal approaches for inclusion and acceptance of autistic individuals; community-available approaches for self-management of mental health; evaluation of adverse mental health outcomes of existing interventions; and improvements in measurement of quality of life, social well-being, and other preferred outcomes in autistic adults. Lay Abstract: Autistic adults commonly experience mental health conditions. However, research rarely involves autistic adults in deciding priorities for research on mental healthcare approaches that might work for them. The purpose of this article is to describe a stakeholder-driven project that involved autistic adults in co-leading and designing research about priorities to address mental health needs. Through a large online survey, two large meetings, and three face-to-face focus group discussions involving over 350 stakeholders, we identified five priorities for mental health research desired by autistic adults. These priorities and preferred outcomes should be used to guide research and practice for autistic adults.